Los vacíos jurídicos de los riesgos laborales del teletrabajo en Ecuador (Tema Central) - Muy Pérez, Efraín Fernando (2021)
The purpose of this article is to explain about of the legal vacuum within the current labour and social security law regulations. There are the labour risks in the telework and the recently introduction of this figure in the Ecuador Law, the treatment is not the correct way, it does not have its own legal regime. These would be subject to the applied for the contingencies of the work risks in general. Because, if the work is do off of the work place dependences, any harmful eventuality is imminent, either as an accident at work or occupational disease. For the effect, is very important analyze the telework figure, the rights and sub rights which comprises and the possible risks of works that could happen for this way of do the work activities. Using a comparative analysis between of the Spanish Law and Colombia Law whose regulation about this topic is so extensive, reduced to manuals, prevention plans and sentences issued of the respective judicial authorities. With this, the need to generate specialized regulations for the coverage of labour risks of telework in Ecuador is exposed, given the particularities that this contractual modality entails.